The double-hit protocol induces HFpEF and impairs myocardial ubiquitin-proteasome system performance in FVB/N mice - Lira, Jose R.; Guymon, Andrew L.; Yang, Liuqing; Sternburg, Jack O.; Giri, Samiksha; Wang, Xuejun (Frontiers in Physiology, 2023)
Heart failure with preserved ejection fraction (HFpEF) is a leading cause of death and disability, with its prevalence surpassing that of heart failure with reduced ejection fraction. Obesity and hypertension are often associated with HFpEF. HFpEF can be modeled through simultaneous metabolic and hypertensive stresses in male C57BL/6N mice provoked by a combination treatment of a high-fat diet (HFD) and constitutive nitric oxide synthase inhibition by Nω-nitro-L-arginine methyl-ester (L-NAME). Ubiquitin-proteasome system (UPS) dysfunction was detected in many forms of cardiomyopathy, but whether it occurs in HFpEF remains unknown. We report successful modeling of HFpEF in male FVB/N mice and, by taking advantage of a transgenic UPS reporter mouse, we have detected myocardial UPS functioning impairment during HFpEF, suggesting a pathogenic role for impaired protein degradation in the development and progression of HFpEF.